1968
DOI: 10.1001/archpedi.1968.02100010241013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local Gamma-A-Immunoglobulins in Immunity

Abstract: OVER THE PAST several years, work in our laboratory has focused on studies of the occurrence and characterization of specific antibodies in secretions of the respiratory tract in an attempt to identify their biological significance in immunity.1-7 These studies arose from the need for a simple biological marker of immunity which could identify individuals most likely to resist overt respiratory tract infection with any of a number of pathogens, particularly viruses. The results of these studies suggest that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

1968
1968
1975
1975

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
6
0
4
Order By: Relevance
“…Evidence is rapidly accumulating that secretory antibody levels are a better indicator of resistance to certain infections, e.g. viral respiratory, and that such antibodies are of the IgA class (Bellanti, 1968;Smith et al, 1966). Susceptibility to recurrent or chronic infections has been attributed to a deficiency of secretory IgA (Buser, Butler, and Du Pan, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is rapidly accumulating that secretory antibody levels are a better indicator of resistance to certain infections, e.g. viral respiratory, and that such antibodies are of the IgA class (Bellanti, 1968;Smith et al, 1966). Susceptibility to recurrent or chronic infections has been attributed to a deficiency of secretory IgA (Buser, Butler, and Du Pan, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…First, certain organ systems such as the gastrointestinal and respiratory tracts normally contain immunocompetent cells (25,26). Local production of immunoglobulin which is principally secretory IgA and specific IgA antibody has been demonstrated (12,(27)(28)(29)(30)(31)(32). Furthermore, studies have demonstrated that protection against reinfection of the respiratory tract correlates better with the presence of local antibody than with the presence of circulating antibody (11).…”
Section: Local Immune Response In Experimental Pyelonephritismentioning
confidence: 99%
“…The phenomenon of local antibody synthesis might account for this apparent discrepancy. 12 Smith, J. W., T. E. Miller, J. A. Barnett, and J. P.…”
Section: Local Immune Response In Experimental Pyelonephritismentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing evidence indicating an important role of secretory IgA in the defence mechanism of the mucosal surface in viral and bacterial infections (Bellanti, 1968;Keller and Dwyer, 1968;Tourville et al, 1969;South et al, 1967;Hashimoto et al, 1970). We have been interested in the local immunity of the intestinal tract against enterotropic viruses.…”
Section: Introductionmentioning
confidence: 99%